2016
DOI: 10.1093/ejcts/ezw364
|View full text |Cite
|
Sign up to set email alerts
|

New tubeless video-assisted thoracoscopic surgery for small pulmonary nodules

Abstract: Tubeless VATS approach for SPNs is feasible in carefully selected patients. Intubation, chest drainage, and/or urinary catheterization may not be necessary in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…was one of the first to introduce nonintubated VATS . Several studies have subsequently shown the feasibility of this approach . which includes patients with small pulmonary nodules (SPN) less than 2 cm in diameter, patients with pulmonary tuberculoma and those with interstitial lung diseases .…”
Section: Nonintubated Anesthesiamentioning
confidence: 99%
“…was one of the first to introduce nonintubated VATS . Several studies have subsequently shown the feasibility of this approach . which includes patients with small pulmonary nodules (SPN) less than 2 cm in diameter, patients with pulmonary tuberculoma and those with interstitial lung diseases .…”
Section: Nonintubated Anesthesiamentioning
confidence: 99%
“…Compared to patients who underwent intubated VATS, the tubeless group showed advantages in the postoperative fasting time, the mean duration of the postoperative hospital stay, and postoperative pain scores (28). In SPN, a study on 34 patients in China (29) showed that tubeless VATS provided definitive diagnosis for all patients and was well-tolerated in the 5 weeks follow-up time, with no need of conversion to endotracheal intubation and no need for re-intervention with chest drain or urinary catheter. Another study comparing 30 patients who underwent non-intubated uniportal VATS with 30 who underwent tubeless VATS found that patients in the tubeless group reported less postoperative pain and had on the average 1.3 days shorter hospital stay (30).…”
Section: Tubeless Vatsmentioning
confidence: 99%
“…However, in 2016 we have seen the development of techniques culminate to take what may have been a 5-day recovery 20 years ago (1), to immediate patient ambulation and oral intake post operatively and patient discharge within 24 hours (2).…”
mentioning
confidence: 99%
“…Recently, this shift of focus has produced some key developments in the field of thoracic surgery; most specifically, minimally invasive anesthesia (6) and tubeless VATS techniques (2). Anesthesia can heavily impact the patient's postoperative speed of recovery.…”
mentioning
confidence: 99%